Perception of Western Musical Modes: A Chinese Study - Fang, Lele; Shang, Junchen; Chen, Nan (Frontiers in Psychology, 2017)
The major mode conveys positive emotion, whereas the minor mode conveys negative emotion. However, previous studies have primarily focused on the emotions induced by Western music in Western participants. The influence of the musical mode (major or minor) on Chinese individuals’ perception of Western music is unclear. In the present experiments, we investigated the effects of musical mode and harmonic complexity on psychological perception among Chinese participants. In Experiment 1, the participants (N = 30) evaluated 24 musical excerpts in five dimensions (pleasure, arousal, dominance, emotional tension and liking). In Experiment 2, the participants (N = 40) evaluated 48 musical excerpts. Perceptions of the musical excerpts differed significantly according to mode, even if the stimuli were Western musical excerpts. The major-mode music induced greater pleasure and arousal and produced higher liking ratings than the minor-mode music, whereas the minor-mode music induced greater tension than the major-mode music. Mode did not influence the dominance rating. Perception of Western music was not influenced by harmonic complexity. Moreover, preference for musical mode was influenced by previous exposure to Western music. These results confirm the cross-cultural emotion induction effects of musical modes in Western music.